Weight gain after kidney donation: Association with increased risks of type 2 diabetes and hypertension. Issue 9 (18th August 2018) - Issa, Naim; Sánchez, Otto A.; Kukla, Aleksandra; Riad, Samy M.; Berglund, Danielle M.; Ibrahim, Hassan N.; Matas, Arthur J.
Abstract: In the general population, obesity is associated with an increased risk of developing hypertension (HTN), type 2 diabetes mellitus (DM), and end‐stage renal disease (ESRD). Therefore, most transplant centers have a body mass index (BMI) threshold for accepting living kidney donors. But there have been no studies of postdonation weight gain trends and any associated risks. We tracked serial BMIs in 940 donors for a median (IQ range) follow‐up of 22.3 (15.4‐35.8) years. We studied the impact of postdonation weight gain in a model adjusted for family history of HTN or DM. Donor characteristics included age, sex, smoking, fasting blood glucose, eGFR, systolic and diastolic BP, and BMI at time of donation and time postdonation. Postdonation weight gain was associated with a significant increase in the relative risk of developing HTN RR 1.93 (95% CI 1.51‐2.46) ( P  < 0.001) and/or DM RR 4.18 (95% CI 2.05‐8.5) ( P  < 0.0001), but not (to date) cardiovascular disease (CVD), reduced eGFR or death. Like the general population, donors gained weight as they aged; a higher BMI was associated with higher incidence of DM and HTN. Postdonation care should include ongoing counseling on the risks of substantial weight gain.